Psychosocial interventions for people with intellectual disabilities and dementia: A systematic review. Issue 5 (27th February 2020) - MacDonald, Steven; Summers, S. J.
Abstract: Background: People with intellectual disability experience a higher prevalence of dementia, at an earlier age, than the general population. The aim of this review was to establish the psychological interventions and outcomes for individuals with intellectual disability and dementia. Methods: A search of eight electronic databases and reference lists of all included articles was conducted using PRISMA guidelines. Data were synthesized using an integrative method. Results: Initial searching produced 2, 331 papers. Twenty‐one studies met the inclusion criteria. Interventions were deductively categorized into behavioural, systemic and therapeutic. All studies reported positive findings for individuals and for the systems which support them, but limited by methodological issues and neglect of the direct experience and impact on individuals themselves. Conclusions: The findings are discussed in relation to the wider literature and evidence base. Future research should aim to adopt methodologically robust designs that are inclusive of the individual experience of people with intellectual disability.